Prevalence of Diabetic Complications in Urban and Rural Population of Punjab - Shafia Naseer, Arooj Malkera, Nadiya Khan, Amer Hassan Siddiqui, Shazia Akbar Khan, Saqib Ali, Mohammad Israr (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The incidence of diabetes is rapidly increasing worldwide and it involves both rural and urban population. Majority of diabetes consequences occur due to its complication that brought a significant burden to pts as well as health care system. Aim: To assess the prevalence of diabetic complications in urban and rural population. Study design: Cross-section descriptive study. Methodology: Present study enrolled 1000 diabetic patients visiting urban and rural health facilities. The type-2 diabetic patients aged 18-70 years were included. Data was collected through questionnaire; data was entered and analyzed in SPSS Vr 24.0 Results: Among 600 patients of urban area, 62.6% were males while among 600 patients of rural area, 82.2% were male. From urban area, 51.2% patients and from rural area, 57.8% patients were above 50 years old. In urban area, 52% patients had infected wounds, 43.8% had cataract, 38.8% had heart problems and 36.1% had stroke. Among rural patients, 48.5% had infected wounds, 38% had diabetic foot, 47.5% had cataract, 33.5% had renal failure and 52.3% had heart problems. In urban population, non-compliance of medication (69%) while in rural population, lack of routine investigations (90.1%) were main factors associated with diabetic complications. Conclusion: Study concluded that diabetic complications were prevalent in both urban and rural areas but rural population was more effected than urban population.